Biological Activity of Lyophilized Chitosan Scaffolds with Inclusion of Chitosan and Zinc Oxide Nanoparticles - Zapata-Ramirez, P (Royal Society of Chemistry, 2024)
The constant demand for biocompatible and non-invasive materials for regenerative medicine in accidents and various diseases has driven the development of innovative biomaterials that promote biomedical applications. In this context, using sol-gel and ionotropic gelation methods, zinc oxide nanoparticles (NPs-ZnO) and chitosan nanoparticles (NPs-CS) were synthesized with sizes of 20.0 nm and 11.98 nm, respectively. These nanoparticles were incorporated into chitosan scaffolds through the freeze-drying method, generating a porous morphology with small (<100 μm), medium (100-200 μm), and large (200-450 μm) pore sizes. Moreover, the four formulations showed preliminary bioactivity after hydrolytic degradation, facilitating the formation of a hydroxyapatite (HA) layer on the scaffold surface, as evidenced by the presence of Ca (4%) and P (5.1%) during hydrolytic degradation. The scaffolds exhibited average antibacterial activity of F1 = 92.93%, F2 = 99.90%, F3 = 74.10%, and F4 = 88.72% against four bacterial strains: K. pneumoniae, E. cloacae, S. enterica, and S. aureus. In vivo, evaluation confirmed the biocompatibility of the functionalized scaffolds, where F2 showed accelerated resorption attributed to the NPs-ZnO. At the same time, F3 exhibited controlled degradation with NPs-CS acting as initiation points for degradation. On the other hand, F4 combined NPs-CS and NPs-ZnO, resulting in progressive degradation, reduced inflammation, and an organized extracellular matrix. All the results presented expand the boundaries in tissue engineering and regenerative medicine by highlighting the crucial role of nanoparticles in optimizing scaffold properties. © 2024 The Royal Society of Chemistry.